Investigation of Snow Compaction Methods and Equipment Conducted for Engineer Research and Development Laboratories, Fiscal Year 1949. Appendix. Tables, Drawings and Photographs. Descriptions of Specialized Procedures. Plan of Test. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MA (1949)
Appendix to report dated Jun 49, AD-495 992.